Dialogue Summary: Building a Primary-Care 'Home' for Every Ontarian - Wilson, MG; Guta, A; Lavis, JN (My University, 2016)
A summary of what was learned from a stakeholder dialogue that addressed problems related to primary-care, options for addressing these problems, key implementation considerations, and next steps for building a primary-care 'home' for every Ontarian.
Keywords: primary-care; home; Ontarian